Efektivitas Model Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar Pendidikan Pancasila di Sekolah Dasar - Abyan Mahesa Kakananta; Amelia Shafa Nur Fadhila; Anindya Fatimah Azzahra; Endrise Septina Rawanoko (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
Learning is a harmony between students, teachers and resources in the learning environment. Learning models play an important role in achieving learning outcomes. This study aims to analyze the effectiveness of the Contextual Teaching and Learning learning model on Elementary School Civics learning outcomes. Contextual Teaching and Learning (CTL) is a learning model that emphasizes the context of the material being studied which is linked to the daily lives of students so that students can understand the material well because they feel familiar with what they do in everyday life. The research approach used is qualitative with data collection techniques, namely literature studies. The results of this study indicate that the Contextual Teaching and Learning learning model is effective for student learning outcomes in the Pancasila Education subject in Elementary Schools.